2011 report on the health of Colorado's forests - Ciesla, William M., author; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2012)
It is once again my pleasure to present the annual report on the health of Colorado's forests. This is the 11th consecutive year we have produced a report on the issues affecting Colorado's forests, as well as the actions we can take to address those issues for the benefit of present and future generations. Over the last 10 years, Colorado's forests have undergone significant changes. I have heard the public and political concerns about the condition of our forests, and related questions regarding what the future holds. The information we have developed and presented in this series of forest health reports, along with our collective experience in managing forested land, addresses these concerns and provides a sound foundation for planning. The fundamental questions we need to ask are What do we want our future forests to look like? and What do we want them to provide for us? Now is the right time to address these questions. We depend on our forests to provide a variety of resources and values; one of the most important is clean water. Forest planning is a long-term process, and the decisions we make today will have profound impacts on the form, function and productivity of our future forests.
2011 forest health report
Report on the health of Colorado's forests
The reports describes "an annual investigation of critical forest health issues, including the identification of priority areas across the state where current forest conditions demand timely action." They are intended to "expand Coloradans' knowledge of and interest in our state's forest resources."
Reports produced by the Colorado State Forest Service in conjunction with Colorado Department of Natural Resources, Division of Forestry.
January 2012.
Keywords: forests and forestry; measurement; Colorado; forest health; forest management